2021
DOI: 10.2478/euco-2021-0036
|View full text |Cite
|
Sign up to set email alerts
|

Music in the Tourism Offering of Rural Regions (The Case of Eastern Croatia)

Abstract: Music is an important element of a destination’s integrated tourism product, especially in rural regions. This fact raises a variety of issues, in particular with regard to the tourism management of rural destinations. Answers are sought to questions on how music can be valorised to help create a distinctive tourism product, making it necessary to analyse the current state of the music offering before objectives can be set and concrete solutions, devised, to accomplish them. This paper explores the music offer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…According to the existing research, it is not difficult to find that the tourism development of cultural resources has been attracted wide discussion [20][21][22][23][24][25]. However, TM has rarely been examined except for a few studies [26][27][28]. Song and Yuan [26] have confirmed that tourism made the style of TM commercialized and diversified, and had an indirect impact on its dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…According to the existing research, it is not difficult to find that the tourism development of cultural resources has been attracted wide discussion [20][21][22][23][24][25]. However, TM has rarely been examined except for a few studies [26][27][28]. Song and Yuan [26] have confirmed that tourism made the style of TM commercialized and diversified, and had an indirect impact on its dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…According to the existing research, it is not difficult to find that the tourism development of cultural resources has been attracted wide discussion [20][21][22][23][24][25]. However, TM has rarely been examined except for a few studies [26][27][28]. Song and Yuan [26] have confirmed that tourism made the style of TM commercialized and diversified, and had an indirect impact on its dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Song and Yuan [26] have confirmed that tourism made the style of TM commercialized and diversified, and had an indirect impact on its dissemination. Rudan and Stipanovic [27]argued that TM was a unique tourism resource, nevertheless, its value has not been effectively explored.…”
Section: Introductionmentioning
confidence: 99%